The Number of Factors in Security Returns - BROWN, STEPHEN J. (Journal of Finance, 1989)
ABSTRACT Both factor analysis of security returns and the analysis of eigenvalues seem to indicate that a market factor explains the major part of security returns. We find that such evidence is consistent with an economy where there are in fact k “equally important” priced factors; eigenvalue analysis in the context of such an economy will lead an investigator to the false inference that the one important “factor” is the return on an equally weighted market index.